Bloody, brutal, and barbaric? wrestling with troubling war texts - Webb, William J. 1957-; Oeste, Gordon K. (Downers Grove, Illinois IVP Academic, an imprint of InterVarsity Press, 2019)
Slaughtering children? Grabbing virgins? -- Where traditional answers do not work -- Where traditional answers do work -- Reading the Bible redemptively -- War rape, part 1: the ugly side -- War rape, part 2: the redemptive side -- War rape meets genocide -- Total-kill hyperbole, part 1: ANE warfare -- Total-kill hyperbole, part 2: Joshua and Judges -- Arguments against hyperbole -- First Samuel 15: hyperbole thesis undone? -- Drive out: an equivalent alternative -- Ancient war atrocities -- Yahweh as reluctant war God: the subversive war texts -- Cross, resurrection, and ascension: the battle is already won -- Jesus as apocalyptic warrior: one word will fell them -- Conclusion: the unfinished justice story.
"Christians cannot ignore the intersection of religion and violence. In our own Scriptures, war texts that appear to approve of genocidal killings and war rape raise hard questions about biblical ethics and the character of God. Have we missed something in our traditional readings? Identifying a spectrum of views on biblical war texts, Webb and Oeste pursue a middle path using a hermeneutic of incremental, redemptive-movement ethics"--
Includes bibliographical references and index
Keywords: War -- Biblical teaching; War -- Religious aspects -- Christianity